Analysis of Factors Affecting Indonesian Tea Exports to Russia - Immanuel, Dixon Christopher; Ayuningsasi, Anak Agung Ketut (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
International trade is a transaction of buying and selling goods between countries, including exports and imports of products. Indonesia, as an agricultural country with a tropical climate, has advantages in producing commodities such as tea. Indonesian tea is exported to various countries, including Russia, although exports experience fluctuations. This research uses secondary data from 1993 to 2022 to analyze the factors that influence Indonesian tea exports to Russia, namely Indonesian tea production, Russian GDP per capita, and the Rupiah exchange rate against the dollar. The research results show that simultaneously, these three variables have a significant effect on Indonesian tea exports to Russia. However, partially, Indonesian tea production and Russian GDP per capita do not have a significant effect on exports, while the Rupiah exchange rate against the dollar has a negative and significant effect.